Diversity, market distribution, and price profile of edible plants traded in the Merapi-Merbabu highlands, Central Java, Indonesia - AWWALIN ROSITA AISYAHTUNNISA; AZ ZAHRA MUTI'AH FADHILAH; CHRISTIN NOVITA PUTRI WIBOWO; CINTA KAMILA GAMA AZIZAH; ADITYA TRIYANTO; AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Aisyahtunnisa AR, Fadhilah AZM, Wibowo CNP, Azizah CKG, Triyanto A, Setyawan AD. 2026. Diversity, market distribution, and price profile of edible plants traded in the Merapi-Merbabu highlands, Central Java, Indonesia. Biodiversitas 27 (7): d270729. https://doi.org/10.13057/biodiv/d270729. Traditional markets connect crop production, household food demand, and local knowledge, yet their agrobiodiversity is rarely documented with transparent commodity-level data. This study inventoried edible plants traded in Ampel, Cepogo, and Selo markets in the Merapi-Merbabu highlands of Boyolali District, Central Java, Indonesia. In May 2026, 104 purposively selected edible-plant traders (40 in Ampel, 34 in Cepogo, and 30 in Selo) were interviewed, and their commodities were directly observed. Recorded fields included market presence, local name, edible part, use category, cultivation status, seasonal availability, reported supplier origin, and price unit. The audited inventory contained 115 market commodity forms representing 94 recorded taxon entries in 35 families. Selo had the highest snapshot richness (76 taxa; 84 commodity forms), followed by Ampel (58; 62) and Cepogo (35; 41). Twenty-eight taxa occurred in all three markets. Pairwise Sørensen similarity was highest between Ampel and Selo (67.2%), followed by Ampel and Cepogo (62.4%) and Cepogo and Selo (52.3%). Using the archived use-category coding, vegetables (39.1%) and herbs, spices, and seasonings (31.3%) dominated the commodity forms. Most forms were cultivated (85.2%), while 12.2% were semi-cultivated and 2.6% wild-sourced. Boyolali was listed as a supplier origin for 91.3% of commodity entries, although origins were nonexclusive and were not weighted by transaction volume. Listed prices ranged from IDR 1,500 to IDR 93,000 per stated sales unit; 69.6% were at or below IDR 20,000, but direct affordability comparisons are not valid because the units were heterogeneous (82 per kg, 28 per bunch, and five in other units). These findings provide a descriptive baseline of market-available edible-plant diversity during the survey period. Repeated seasonal sampling, standardized market coverage, voucher-supported identification, standardized price units, and quantified commodity flows are needed for stronger ecological, cultural, and economic inference.